Lipid classes, fatty acid composition and antimicrobial properties of brown algae Lobophora tsengii D. Tien & Z. Sun collected at Bach Long Vi island - Dam Duc Tien; DAO , THI KIM DUNG; DANG, THI TUYET; TRAN, THI THU THUY; HOANG, THI MINH NGUYET; PHAM, QUOC LONG; Phuong, Doan Lan (Vietnam Journal of Science and Technology, 2025)
Lobophora tsengii D. Tien & Z. Sun is a brown algae species that was discovered for the first time in 2020 at Bach Long Vy island (Bailongwei), Hai Phong province, Vietnam, In this paper, the lipid classes, fatty acid composition, and antimicrobial activities of Lobophora tsengii D.Tien & Z.Sun were described. The unsaturated fatty acid content accounted for 53.11 % of the total fatty acids, of which arachidonic acid (AA) and eicosapentaenoic acid (EPA) contents reached 8% and 11.46%, respectively. The polar lipid (PL) was the highest content class (43.47 %) in total lipid. Interestingly, the polar lipid fraction contains only the four most abundant phospholipid classes in mammals: phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylserine (PS) and phosphatidylethanol amine (LPE). Among them, PE and PC contents are equivalent over 30 % and LPE content (18.86 %) is twice higher than PS content (9.29 %). Evaluation of microbial activities against seven microorganims strains indicated that the extract of L. tsengii showed a strong inhibition against Staphylococcus aureus with IC50 value of 54.95 ± 1.38 µg/ml.